Factors affecting the decrease of gear noise - Kramek, Agnieszka; Gumieniak, Justyna (Advances in Mechanical and Materials Engineering, 2022)
Vibroactivity that occurs during the operation of toothed gears has many sources. Shaping the acoustic conditions is possible at the design and construction stage. Additionally, high economic and operational requirements force us to search for innovative research methods in the field of simulation techniques. The causes of parametric vibrations of gears have internal and external causes, which are most often caused by the impact of other working units of machines and are difficult to eliminate. The most important factors influencing the noise level during the operation of toothed wheels are: gear type, tooth profile, pitch - module, relief angle, tooth engagement and displacement phase resulting from the position of the rolling diameters on the active section of the buttress, changes in the tooth profile, degree of gear coverage, inter-tooth clearance , tooth load, quality level, surface finish (roughness), runout and unbalance, gear ratio, resonance, lubricant viscosity, and gear housing.